Durvalumab, Tremelimumab, and Platinum Chemotherapy in EGFR Mutation–Positive NSCLC: An Open-Label Phase 2 Trial (ILLUMINATE) - Chee Khoon Lee, PhD; Bin-Chi Liao, MD; Shalini Subramaniam, MMed (Clin Epi); Chao-Hua Chiu, MD; Antony J. Mersiades, MMed (Clin Epi); Chao-Chi Ho, MD, PhD; Chris Brown, MBiostats; Chun-Liang Lai, MD, PhD; Brett G.M. Hughes, M.B.B.S. (Hons); Tsung-Ying Yang, MD, PhD; Ken O’Byrne, MD; Yung-Hung Luo, MD, PhD; et al. (JTO Clinical and Research Reports)
Introduction: EGFR-mutant NSCLC is associated with low mutation burden and low levels of PD-L1 expression. We conducted a phase 2 trial to determine the efficacy of durvalumab, tremelimumab, and platinum-pemetrexed in EGFR-mutant NSCLC after progression with EGFR tyrosine kinase inhibitors (TKIs). Methods: Participants were treated with induction durvalumab, tremelimumab, and platinum-pemetrexed, followed by durvalumab-pemetrexed maintenance. Participants were divided into two cohorts: (1) EGFR exon 20 T790M negative (T790M−, progressing on either first-line osimertinib, or on a single line of first/second generation TKI), and (2) T790M positive (T790M+, progressing on greater than or equal to 1 lines of TKI, including osimertinib). The primary endpoint was the confirmed objective response rate (ORR) assessed by the investigators. Progression-free survival and safety were secondary outcomes. Results: One hundred participants from Australia and Taiwan were enrolled. Median follow-up was 26 months with 88% and 96% experiencing progression events for T790M− and T790M+, respectively. The ORR for T790M− was 31% (95% confidence interval: 20–45), including two complete responses. The ORR for T790M+ was 21% (95% confidence interval: 12–34). Median durations of response were 9.5 months and 6.3 months for T790M− and T790M+, respectively; median progression-free survival rates were 6.5 months and 4.9 months, respectively. For T790M−, ORR was 27% for 50% or higher PD-L1 (n = 22) and 0% for less than 50% PD-L1 (n = 10), respectively. For T790M+, ORR was 17% for 50% or higher PD-L1 (n = 24). The safety profile was consistent with previous reports. Conclusions: Durvalumab, tremelimumab, and platinum-pemetrexed had modest anti-tumor activity in EGFR-mutant NSCLC after progression on TKI. The T790M− cohort had higher ORR and a longer duration of response. Immune adverse events were not increased with tremelimumab. The clinical registration number of this trial is NCT03994393.